The Effect of Leadership Style and Organizational Culture and Work Motivation on Lecturer Performance - Kamiliya Atikah; Nurul Qomariah (Universitas Muhammadiyah Jember, 2020)
Employee performance is an important thing in an organization. Whether an organization is good or not depends on the performance of employees. Likewise with tertiary institutions, one thing that needs to be considered is the performance of the lecturers. This study aims to determine the effect of leadership style and organizational culture and work motivation on the performance of lecturers at the University of Muhammadiyah Jember. The population of this research is all lecturers who work at the University of Muhammadiyah Jember, amounting to 320 people. The sample size is calculated as 15% of the total population, so it is known that the sample size is 45 people. Sampling was done by random sampling technique. Data were analyzed using analyzed using the PLS-based SEM method with the help of the WarpPLS 5.0 application. The results showed that: leadership style has a significant effect on lecturer performance with a positive path coefficient value of 0.367 and a significance value of 0.003. Organizational culture has no significant effect on lecturer performance with a positive path coefficient value of 0.023 and a significance value of 0.439. Work motivation has a significant effect on employee performance with a positive path coefficient value of 0.57 and a significance value of 0.001.